Removal of U(VI) by Micrococcus aloeverae: condition, kinetic and mechanism studies - Xingming Gao; Mengmei Ye; Wenxin Li; Yong Lu; Lingzhi Bao (Results in Chemistry)
The ecological and environmental implications arising from the release of uranium during nuclear industry and mining activities are subject to considerable apprehension. Employing microbial agents for uranium remediation offers a promising and efficient alternative to tackle soil or wastewater contamination caused by uranium. In this work, we successfully isolated and identified a highly uranium-tolerant strain GX01, identified as Micrococcus aloeverae, from soil samples collected at a uranium mining site. The state, kinetics and mechanism of U(VI) removal by Micrococcus aloeverae were then investigated. The strain demonstrated both biotransformation and biosorption ability to U(VI), with an excellent removal capacity of 123 mg/g for U(VI) at pH 6.0. The involvement of carboxyl, amide, and amine groups in the biosorption processes was determined by Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) analysis. Kinetic and isothermal studies demonstrated that the biosorption of U(VI) by Micrococcus aloeverae followed a pseudo-second order mode and Langmuir model. These results initially established Micrococcus aloeverae as an idea candidate for radionuclide removal.